PERANCANGAN OTOMATISASI JARINGAN BERBASIS WEB DENGAN DJANGO (STUDI KASUS PT.PLATINUM CITRA INDONESIA) - Abdul Aziz Aziz; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The development of digital technology as it is today is growing very fast, especially in the field of information systems with the aim of converting data sources into various kinds of information needed by users. In simple terms it can be said that the data is processed into information. PT. Platinum Citra Indonesia was established on February 1, 2013 until now. Platinum Citra Indonesia is a company engaged in internet service provider services located in the Sepatan area, Tangerang Regency. Due to the lack of experts at the company, the support team often finds it difficult to configure the router. The application program to be built is a web-based network automation that can facilitate and be effective in updating configurations, updating operating systems (OS), updating usernames and passwords, as well as performing backup and restore configurations on customer routers simultaneously, with commands typed in one dashboard. web. With this application, it is expected to be effective in updating configurations, updating operating systems (OS), updating usernames and passwords, as well as performing backup and restore configurations on customer routers simultaneously, with commands typed in a web dashboard. The programming language used is the Python Framework Django and the database uses SQLite, the testing method uses Blackbox Testing.